Cumulative access to print books improves literacy achievement: Evidence from a five-year randomized trial in high-poverty schools - Geoffrey D. Borman; Hyunwoo Yang (Proceedings of the National Academy of Sciences, 2026)
For more than a century, studies have shown that children who grow up in homes with more books achieve higher levels of academic success, yet it remains unclear whether books themselves improve learning or simply reflect broader socioeconomic advantages. Skill-development theory holds that greater access to books directly improves literacy through increased print exposure and reading practice, whereas the cultural capital account suggests books are indicators of broader family resources, including parental education, academic norms, and enrichment opportunities, that promote achievement independently of the books themselves. To provide causal evidence, we conducted a school-level randomized controlled trial of a program that builds children’s home libraries. In 2018, we randomly assigned 60 high-poverty public elementary schools to treatment or control groups. Students in 30 treatment schools received four book distributions over 5 y, averaging about seven books per distribution, and prominently including high-interest and culturally relevant titles; students in 30 control schools received none. Tracking students from 2018–19 through 2022–23, we find a statistically significant intention-to-treat impact on reading achievement of d = 0.100 and a larger d = 0.207 advantage for those completing the full 5-y program. These impacts correspond to approximately 25 to 32% and 52 to 65% of a typical year’s learning, respectively. The largest benefits are concentrated among students who received books across all distributions, indicating that cumulative exposure drives the strongest impacts. These findings provide evidence supporting skill-development theory and highlight a scalable strategy for improving literacy outcomes in high-poverty urban schools.